2016
DOI: 10.1016/j.virol.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

HPV31 utilizes the ATR-Chk1 pathway to maintain elevated RRM2 levels and a replication-competent environment in differentiating Keratinocytes

Abstract: Productive replication of human papillomaviruses (HPV) is restricted to the uppermost layers of the differentiating epithelia. How HPV ensures an adequate supply of cellular substrates for viral DNA synthesis in a differentiating environment is unclear. Here, we demonstrate that HPV31 positive cells exhibit increased dNTP pools and levels of RRM2, a component of the ribonucleotide reductase (RNR) complex, which is required for de novo synthesis of dNTPs. RRM2 depletion blocks productive replication, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 71 publications
3
63
0
5
Order By: Relevance
“…(55, 56). Numerous studies have demonstrated that HPV exploits both the ATM and ATR DDR pathways in order to successfully replicate its genome (8, 12, 57). In contrast, little is known regarding the importance of HPV’s interaction with the DNA-PK pathway for the viral life cycle.…”
Section: Dna Damage Repair Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…(55, 56). Numerous studies have demonstrated that HPV exploits both the ATM and ATR DDR pathways in order to successfully replicate its genome (8, 12, 57). In contrast, little is known regarding the importance of HPV’s interaction with the DNA-PK pathway for the viral life cycle.…”
Section: Dna Damage Repair Pathwaysmentioning
confidence: 99%
“…Activation of the ATR/Chk1 pathway is also required for the stable maintenance of viral episomes (8, 12, 14), and recent studies have found that ATR/Chk1 activation is also required for productive viral replication (8, 12). Both E7 and E1 can independently activate the ATR/Chk1 pathway (8, 82, 87).…”
Section: Hpv Manipulation Of the Dna Damage Response Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Checkpoint kinase 1 (Chk1) is one of the key regulators in the signal transduction pathway set in motion in response to DDR, which activates different cell cycle checkpoints including G1-S, intra-S, G2-M, and mitotic spindle checkpoints, contributing to the maintenance of the genomic stability. Significant progress has been made toward the understanding of Chk1 regulation and its implications in viral infection, cancer etiology, and therapy [19][20][21]. Chk1 has been found to be overexpressed in a variety of human malignancies, including colon, liver, breast, and gastric carcinoma, etc.…”
Section: Introductionmentioning
confidence: 99%